Development of Allometric Model for Estimating Biomass and Carbon Storage of Hybrid Eucalyptus (E. grandis x E. urophylla) in Industrial Plantation Forests of North Sumatra Province - Marnaek, Ronald Hot; Setiawan, Yudi; Hermawan, Rachmad; Muhdin (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Hybrid eucalyptus (E. grandis × E. urophylla) plays an important role in the global carbon cycle because it grows so fast that it is necessary to know how much biomass and carbon are produced. This study aims to develop an allometric equation for estimating the biomass and carbon content stored in Eucalyptus stands. Data were obtained through destructive sampling of 75 trees, then dried in an oven and analyzed to get the most appropriate biomass value and allometric model. The study results showed that the developed polynomial model correlated well with DBH to predict biomass with an R-squared of 97.50. Age 1 with an average diameter of 3.23 cm = 2.50 tons C/ha or 9.17 tons of CO2e, age 2 with an average diameter of 9.33 = 21.30 tons C/ha or 78.16 tons CO2e, age 3 with an average diameter of 9.49 cm = 22.50 tons C/ha or 82.57 tons CO2e, age 4 with an average diameter of 11.62 cm = 38.61 tons C/ha or 141.68 tons CO2e, age 5 with an average diameter of 12.63 cm = 46.42 tons C/ha or 170.37 tons CO2e. The carbon stock results show that as the age of the stand increases, the carbon reserves stored also increase. Keywords: allometric model, biomass, carbon stock, hybrid eucalyptus